Correlational analysis between the Institutional Improvement Plans and Educational Management in colombian institutions (Journal SCIENCEVOLUTION, 2024)
Improvement plans and educational management are considered a crucial process for the advancement and quality of the educational action from the institutions, it is emphasized that these are subject to the educational standards and norms of Colombia with the purpose of improving the academic performance of the student population. Therefore, this research work dealt with the correlation between the variables: Institutional Improvement Plans and Educational Management in two Colombian educational institutions: Portal Campestre Norte and Villas de San Juan de Girón de Colombia, from two perspectives: educational management and the concepts adopted by the Ministry of National Education. The quantitative method was used, correlational scope and a descriptive and inferential statistical analysis, with a non-probabilistic and intentional sample of 52 teachers and 3 directors; for data collection the survey technique was used and the instruments were the structured questionnaire and evaluation rubric. As a result, the dimensions of the variables showed a significant relationship because the p-values obtained in Spearman's Rho test (0.002) were less than 0.05.  This leads to the conclusion that there is a relationship between Educational Management and Institutional Improvement Plans. Therefore, it is recommended to integrate Improvement Plans as key tools to systematize education, with shared responsibilities among directors, educators and academic council.
Keywords: Educational management; Educational leadership; Institutional improvement plans